2018
DOI: 10.1128/aem.00283-18
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival and Thermal Death Kinetics of Enterohemorrhagic Escherichia coli Serogroups O26, O103, O111, and O157 in Wheat Flour

Abstract: Wheat flour has been associated with outbreaks of enterohemorrhagic (EHEC), but little is known on EHEC's survival during storage and thermal processing. The objective of this study was to determine long-term viability and thermal inactivation kinetics of EHEC serogroups O26, O103, O111, and O157. Wheat flour samples were inoculated with a cocktail of five strains of a single serogroup and stored at 23 and 35°C. Inoculated samples were heated at 55, 60, 65, and 70°C. Viability was determined by plate counting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
8
28
0
Order By: Relevance
“…Thus in the present paper, we included assessing Salmonella long-term survival at room temperature and thermal death kinetics at 55, 60, 65, and 70°C in wheat flour. In addition, Salmonella survival was studied at 35°C for comparison with similar data on EHEC obtained in our previous study (Forghani et al, 2018). These temperatures were selected because it was unlikely that they had negative influence on the wheat flour properties (Ozawa et al, 2009; Khamis, 2014; Sudha et al, 2016) for the amount of time that they were used in the study.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Thus in the present paper, we included assessing Salmonella long-term survival at room temperature and thermal death kinetics at 55, 60, 65, and 70°C in wheat flour. In addition, Salmonella survival was studied at 35°C for comparison with similar data on EHEC obtained in our previous study (Forghani et al, 2018). These temperatures were selected because it was unlikely that they had negative influence on the wheat flour properties (Ozawa et al, 2009; Khamis, 2014; Sudha et al, 2016) for the amount of time that they were used in the study.…”
Section: Discussionmentioning
confidence: 81%
“…The information available about EHEC long-term survival in wheat flour was very limited until our recent study (Forghani et al, 2018), in which we reported survival and thermal inactivation of EHEC serovars O26, O103, O111, and O157 in wheat flour. Such information was important to the industry due to the fact that product composition such as the unique composition of wheat flour may affect the rate of microbial inactivation (Santillana Farakos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheat flour is an agricultural product which can be contaminated with bacterial pathogens during primary production and the milling process (34,37). The low-moisture content (aw <0.6) of wheat flour does not support the growth of bacterial pathogens, however some bacterial pathogens can survive in this low-moisture environment (21,25) and can multiply in highermoisture raw flour-based products such as batter or cookie dough (43). Ready-to-Eat (RTE) wheat flour-based products are usually subject to thermal treatments such as baking, steaming, and frying, all of which would contribute to the inactivation of bacterial pathogens before consumption.…”
Section: Highlightsmentioning
confidence: 99%